Associations of smoking and alcohol consumption with impaired β‐cell function in Chinese men. (14th July 2015) - Xu, Min; Zhou, Yulin; Xu, Baihui; Sun, Jichao; Wang, Tiange; Lu, Jieli; Lai, Shenghan; Bi, Yufang; Wang, Weiqing; Ning, Guang
Abstract: Background: The aims of the present study were to examine the association of cigarette smoking and alcohol consumption with impaired β ‐cell function in Chinese men, particularly the interaction of smoking and alcohol consumption on impaired insulin secretion. Methods: A population‐based cross‐sectional study was performed in 3957 Chinese men aged ≥40 years. The homeostatic model assessment of β ‐cell function (HOMA‐ β ) was calculated, and impaired β ‐cell function was defined as less than the lowest quartile HOMA‐ β cut‐off point. Results: The prevalence of impaired β ‐cell function in current smokers and heavy drinkers (≥200 g/week) was significantly higher than in non‐smokers and non‐drinkers, respectively. Compared with non‐smoking, current smoking had an exacerbating relationship with impaired β ‐cell function (odds ratio [OR] 1.78; 95% confidence interval [CI] 1.47–2.15; P < 0.001). No significant association was found between impaired β ‐cell function and former smoking ( P = 0.21), although low and heavy drinking were associated with an increased risk of impaired β ‐cell function (OR 1.40 [95% CI 1.07–1.81] and 2.14 [95% CI 1.77–2.58], respectively) compared with non‐drinking. The combination of current smoking and heavy drinking was associated with the highest risk of impaired β ‐cell function (OR 3.16; 95% CI 2.43–4.12; P < 0.0001) after adjustment for confounders. We did not detect an additive interaction between current smoking and heavy drinking on the association with impaired β ‐cell function. Conclusions: Cigarette smoking and alcohol consumption were significantly and independently associated with impaired β ‐cell function in Chinese men.